Situation Report: Bulgaria, 26 February 1979 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu Visits Zhivkov Dragoycheva Answers Yugoslav Criticism over Macedonia Balkan Specialists Appointed Ambassador to Greece New Decree on Tourism